Spatial quantile regression in analysis of mortality - Trzpiot, Grażyna; Orwat-Acedańska, Agnieszka (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The paper concerns mortality in Poland. The aim of the article is to identify factors determining average life length of men and women in 66 subregions of Poland. We use spatial quantile regression methodology which allows studying dependencies between variables in different quantiles of the response distribution. Moreover, this statistical tool is robust against violations of the classical regression assumption about the multidimensional distribution of error term.